2022
DOI: 10.1186/s41232-022-00238-2
|View full text |Cite
|
Sign up to set email alerts
|

Resolving the conflicts around Par2 opposing roles in regeneration by comparing immune-mediated and toxic-induced injuries

Abstract: Background Different factors may lead to hepatitis. Among which are liver inflammation and poisoning. We chose two hepatitis models, typical for these two underlying causes. Thus, we aimed to characterize the role of protease-activated receptor 2 (Par2) in liver regeneration and inflammation to reconcile Par2 conflicting role in many damage models, which sometimes aggravates the induced damage and sometimes alleviates it. Methods WT and knockout (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 66 publications
1
3
0
Order By: Relevance
“…Furthermore, a study combining ApoE deletion with BM replacement experiments demonstrated that Par2KO mice exhibited a decreased atherosclerotic phenotype compared to control mice [ 88 ]. This study indicated that the atherosclerotic phenotype is mediated by Par2 activation in the immune system, which aligns with our recent work demonstrating the role of leukocyte Par2 in ConA-induced hepatitis [ 23 ].…”
Section: Introductionsupporting
confidence: 91%
See 3 more Smart Citations
“…Furthermore, a study combining ApoE deletion with BM replacement experiments demonstrated that Par2KO mice exhibited a decreased atherosclerotic phenotype compared to control mice [ 88 ]. This study indicated that the atherosclerotic phenotype is mediated by Par2 activation in the immune system, which aligns with our recent work demonstrating the role of leukocyte Par2 in ConA-induced hepatitis [ 23 ].…”
Section: Introductionsupporting
confidence: 91%
“…In the ConA model, we demonstrated that when Par2 was expressed in the immune system, the inflammatory response was intensified, as shown by Song et al and Li et al However, when Par2 was expressed in the tissue and not in the immune cells, the livers were protected from the damage induced by ConA. However, when we attempted to replicate these findings in the CCl 4 model, we found that immune cell Par2 did not affect the damage, and liver recovery was completely dependent on Par2 expression in hepatocytes [ 23 ]. These observations led us to the conclusion that Par2 has two roles: in leukocytes, it promotes an inflammatory response, and in the target tissue, it promotes regeneration.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations